THE POTENTIAL OF BUFFALO LIVESTOCK DEVELOPMENT BY OPTIMIZING THE GRAZING LANDS MANAGEMENT IN RIAU PROVINCE - Syafitri, Winda; S. Purba, Hastuti Handayani (Proceeding Buffalo International Conference, 2013)
SinceÂ  2008 to 2012, the number of buffalo populations in Riau province continues to decline. Based on the statistical data, in 2008 the buffalo populations number in Riau reached 77. 271, and in 2012 the numbers fell to 47.808. The Problem of buffalo livestock in Riau province are quite variable, among other: traditional maintenance, reduced of grazing land , the less priorities of the local government where the cattle livestock development are more priority than the development of buffaloes livestock. The presence of grazing lands are very important to support the buffalo livestock productivity. The grazing land is a medium of buffalo livestock production with low cost input management system (low cost management). There are some potential grazing lands in Riau, with large about 184.642 ha. Therefore revitalization and expansion of grazing land in some potential areas in Riau province, will become one part of buffalo livestocks development patterns that utilize forage in the grazing land as food resource. So that, it have been the time, to manage the grazing lands in Riau province in a Region Government Legislation (PERDA). It will be very important to ensure the sustainability of buffaloes livestock business in Riau Province.